Viral hepatitis in Bucharest. - Paquet, C. (World Health Organization, 1993)
A seroprevalence survey of viral hepatitis was conducted in Bucharest, Romania, between April and July 1990 on a systematic sample of 1355 persons drawn from the general population and groups at higher risk of infection. Sera were tested for hepatitis A, B, and C (HAV, HBV and HCV, resp.) markers using an enzyme-linked immunosorbent assay (ELISA) method. The prevalences of HAV and HBV markers were high in all groups. A total of 47% of the adults from the general population and 39.8% of the children aged 0-16 years had at least one HBV marker. Of the pregnant women 7.8% were positive for hepatitis B surface antigen. Among infants (0-3 years of age) living in orphanages, the prevalence of at least one HBV marker was 54.6%. The findings also confirmed that HCV was circulating in Romania. The results are consistent with national surveillance data and confirm that viral hepatitis is a major public health problem in Romania. Preventive measures will have to include HBV immunization of infants, with an appropriately targeted immunization strategy being determined through further epidemiological studies.